Civil society in a global multistakeholder policy-making process : the case of the internet and netmundial - Haristya, Sherly (2019)
The concern over critical Internet resources has led to a development of the multistakeholder model for Internet governance. A key stakeholder is civil society, which is recognised for bringing a diversity of views to contribute to the democratisation of global governance. Although deliberative democracy theory prescribes diversity of civil society and thus inclusiveness as the normative conditions for civil society to be able to influence the global policy-making space, there is a tension between them. The diversity of civil society poses a challenge for the groups to operate cohesively in order to influence policy-making space. Civil society sometimes sacrificed inclusiveness in order to increase their influence in a policy-making space. This tension suggests a gap in the theory. Primary data were collected around the NETmundial meeting—the first global multistakeholder consensus-building process in the Internet governance field held in Brazil in 2014—using observation, online documents from the website and several mailing lists of civil society networks, as well as face-to-face and online semi-structured interviews and analysed qualitatively. This study found that the development of civil society’s joint position needed to attend to the various views held by the participating civil society actors on their terms of engagement in the NETmundial in conjunction with the short- and long-term expected efficacy in the related process and in the larger global governance arrangements. This measure needs to be taken in order to enable the joint position of civil society to be legitimately influential when raised to the policy-making stage. These findings modified the deliberative democracy theory by expanding the concept of output legitimacy to cover both short- and long-term expected efficacy of civil society in the related multistakeholder consensus-building process and in the larger global governance arrangements in order to tackle the tension between inclusiveness and efficacy.